High School and large scale evaluations in the brazilian educational context (Research, Society and Development, 2021)
The essay now under report aims to analyze the evolution of High School (HS), outlining its relationship with the large-scale assessments implemented in Brazil in the mid-1990s. ? Is this level the stepping stone to university or vocational training? Based on what parameters is this level of education discussed and implemented? What do evaluations express? Could these large-scale measurements offer the necessary elements to think of a proposal for this teaching for all Brazilian adolescents and young people? As for the methodology, theoretical support was sought from renowned authors such as Mello (1999), Kuenzer (1997), Ramos (2011), Freitas (2004), Maggio (2006), as well as consultations in documents such as laws, school censuses and reports . The results showed that there were advances in Brazilian High School, such as the increase in enrollments, but that old problems remain and that new difficulties are expressed – persistence of high dropout and failure rates; lack of economic conditions for students in public schools; disinterest; etc. In addition, the expansion bears the mark that reproduces regional inequality, gender, color, race and type of offer of general education for the elites and high school technicians for the children of workers, expressing the duality rooted in this educational stage. The considerations point to the need for changes in education, including the conditions of teacher training, with the exception of the evaluative instruments, seeking to apprehend the identity of High School.